A preliminary psychometric evaluation of Music in Dementia Assessment Scales (MiDAS). (June 2014) - McDermott, Orii; Orgeta, Vasiliki; Ridder, Hanne Mette; Orrell, Martin
ABSTRACT Background: Music in Dementia Assessment Scales (MiDAS), an observational outcome measure for music therapy with people with moderate to severe dementia, was developed from qualitative data of focus groups and interviews. Expert and peer consultations were conducted at each stage of the scale development to maximize its content validity. This study aimed to evaluate the psychometric properties of MiDAS. Methods: Care home residents with dementia attended weekly group music therapy for up to ten sessions. Music therapists and care home staff were requested to complete weekly MiDAS ratings. The Quality of Life Scale (QoL-AD) was completed at three time-points. Results: A total of 629 (staff = 306, therapist = 323) MiDAS forms were completed. The statistical analysis revealed that MiDAS has high therapist inter-rater reliability, low staff inter-rater reliability, adequate staff test-retest reliability, adequate concurrent validity, and good construct validity. High factor loadings between the five MiDAS Visual Analogue Scale (VAS) items, levels of Interest, Response, Initiation, Involvement, and Enjoyment, were found. Conclusions: This study indicates that MiDAS has good psychometric properties despite the small sample size. Future research with a larger sample size could provide a more in-depth psychometric evaluation, including further exploration of the underlying factors. MiDAS provides a measure of engagement with musical experience and offers insight into who is likely to benefit on other outcomes such as quality of life or reduction in psychiatric symptoms.